Superior Approach of Recurrent Laryngeal Nerve: Review of the Literature. (18th December 2019) - Fatogoma Issa, Koné; Sidiki, Dao; Naouma, Cissé; Kassim, Diarra; N'Faly, Konaté; Djibril, Samaké; Neuilly, Tafo; Abdoul Wahab, Haidara; Boubacary, Guindo; Siaka, Soumaoro; Kadidiatou, Singaré; Samba Karim, Timbo; et al.
Abstract : The identification and dissection of the recurrent laryngeal nerve is essential to guarantee its anatomical and functional integrity. The superior approach of the recurrent nerve is a reliable surgical alternative. Various indications are recognized with a reliable landmark. This is the entry point into the larynx under the inferior horn of the thyroid cartilage. The limits of this technique, namely, the extralaryngeal divisions and the hemorrhages encountered at the point of entry of the larynx are a source of morbidity of the recurrent laryngeal nerve. A careful dissection, respect for the surgical steps, and the surgeon's experience are guarantees of a good result. We wanted through a review of the literature and our experience in the superior approach to discuss surgical indications, to identify landmarks at the point of entry of the larynx, to determine the limits of this approach, and to take precautions to mitigate the risk of recurrent laryngeal nerve injury.